ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RGEC PADA PT BANK CENTRAL ASIA TBK PERIODE 2020-2024 - Vina Maudina; Chitra Septiani; Dani Galuh Permana; Hani Hatimatunnisani (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2026)
This study analyzes the financial soundness of PT Bank Central Asia Tbk (BCA) using the Risk-Based Bank Rating (RBBR) approach through the RGEC method, which includes Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital during the period 2020–2024. The study applies a descriptive quantitative method using secondary data from annual financial statements and corporate governance reports. The results indicate that BCA’s financial soundness during the 2020–2024 period is classified as “Very Healthy.” Based on the RGEC method, the average Non-Performing Loan (NPL) is 0.7%, the Good Corporate Governance (GCG) aspect obtains Rating 1, Return on Assets (ROA) is 3.2%, and the Capital Adequacy Ratio (CAR) is 25,4%, all of which obtain Rating 1. This condition indicates that BCA has strong financial resilience and effective banking management.